Factors associated with restrained eating and validation of the Arabic version of the restrained eating scale among an adult representative sample of the Lebanese population: a cross-sectional study - Sylvia Saade; Souheil Hallit; Chadia Haddad; Rabih Hallit; Marwan Akel; Karl Honein; Maria Akiki; Nelly Kheir; Sahar Obeid (Journal of Eating Disorders, 2019)
Abstract Background Previous research suggests that restrained eating is problematic in Lebanon and is associated with the occurrence of clinically diagnosed eating disorders. Because of the alarming prevalence and severity of these disorders, the aim of this study is to investigate factors that may contribute to restrained eating in adults among a representative sample of the Lebanese population. Methods This is a cross-sectional study conducted between January and May 2018; 811 adult participants were enrolled from all Lebanese districts. The Dutch Restrained Eating scale was used to measure body disturbance. The factors that were assessed in the questionnaire were body dissatisfaction, self-esteem, perceived stress, anxiety, depression, emotion regulation, emotional eating and adult attachment styles. Results The mean age of the participants was 27.59 ± 11.76 years, and included 66.5% females. In the absence of a cutoff value for the Dutch Restrained Eating scale, we took the median (2.6) as the cutoff value. The results showed that 391 (48.3%) had restrained eating. The Dutch Restrained Eating scale items converged over a solution of one factor that had an Eigenvalue over 1, explaining a total of 60.69% of the variance (Cronbach’s alpha was high =0.928). The linear regression results, taking the Dutch restrained eating scale as the dependent variable, showed that being a female (Beta = 0.31), increased age (Beta = 0.01), higher body mass index (Beta = 0.01), an intermediate monthly income (Beta = 0.25), higher body dissatisfaction scores (Beta = 0.03), higher adult anxiety attachment style (Beta = 0.008), higher emotion regulation cognitive reappraisal facet (Beta = 0.01), feeling pressure from TV/magazine to lose weight (Beta = 0.45) and practicing sport activities (Beta = 0.41) were associated with higher restrained eating scores. Conclusion Our findings show that numerous factors are associated with restrained eating in the Lebanese community. They include body dissatisfaction, cognitive reappraisal, female gender, eating attitudes, social media pressure and adult attachment. Therefore, the development of prevention strategies directed at an improved body image perception and increasing knowledge about factors that might influence this body image and critical thinking regarding media images is warranted, with the ultimate goal of promoting healthier choices in the Lebanese population.